Reformulation of soy sauce to reduce sodium content and assessment of manufacturer readiness, consumer acceptance, and shelf life - Harun, Zaliha; Shahar, Suzana; Haron, Hasnah; You, Yee Xing; Mohamad Taib, Aida Farzana; Abdul Manan, Musaalbakri; Wan Ibadullah, Wan Zunairah; Mohamad, Hamdan; Michael, Viola; Ong, Ying Qian; Mastor, Syazwani; Burt, Hattie; et al. (Nature Research, 2025)
Soy sauce is a major source of dietary sodium in Malaysia. Reformulating soy sauce to reduce its sodium content may help lower population salt intake. This study aimed to (1) assess sodium content of Malaysian soy sauces; (2) evaluate manufacturer readiness for reformulation; (3) develop reduced sodium soy sauce formulations; and (4) determine consumer acceptability and shelf life stability. A mixed-methods study was conducted in two phases: (1) needs assessment through sodium analysis of 102 soy sauces from supermarkets and interviews with 19 employees; and (2) development of reduced sodium soy sauce formulations, followed by consumer sensory testing (n = 52) and accelerated shelf life assessment. Salty (4987 ± 1429 mg/100 g) and light soy sauces (5710 ± 1488 mg/100 g) contained significantly higher sodium than sweet soy sauces (3368 ± 863 mg/100 g; p < 0.05). Manufacturers acknowledged the importance of salt reduction but cited barriers including consumer acceptance, regulatory requirements, costs, and limited research and development capacity. Among the reformulated products, soy sauce with 9% salt plus yeast extract (≈3600 mg sodium/100 g) was most preferred and remained shelf-stable for one year. Reformulation of soy sauce with lower sodium content is feasible without compromising safety or palatability. Wider adoption by manufacturers, supported by incentives and regulatory adjustments, could reduce population salt intake in Malaysia.